2014
DOI: 10.1093/schbul/sbt154
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analyses of Blood Homocysteine Levels for Gender and Genetic Association Studies of the MTHFR C677T Polymorphism in Schizophrenia

Abstract: Previous studies suggest that elevated blood homocysteine levels and the methylenetetrahydrofolate reductase (MTHFR) C677T polymorphism are risk factors for schizophrenia. However, the effects of gender and MTHFR C677T genotypes on blood homocysteine levels in schizophrenia have not been consistent. We first investigated whether plasma total homocysteine levels were higher in patients with schizophrenia than in controls with stratification by gender and by the MTHFR C677T genotypes in a large cohort (N = 1379)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
56
2
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(65 citation statements)
references
References 84 publications
5
56
2
2
Order By: Relevance
“…For example, we observed elevated blood homocysteine levels in individuals with schizophrenia and provided evidence of a causal relationship between elevated blood homo-cysteine levels and schizophrenia risk. 6,7 In addition, we showed that the methylenetetrahydrofolate reductase (MTHFR) C677T polymorphism, which causes reduced enzyme activity and elevated homocysteine levels, and common polygenic variants that are associated with plasma homo cysteine levels are risk factors for schizophrenia in the Japanese population. 6,8 Furthermore, we showed aberrant DNA methylation in patients with schizophrenia, not only in peripheral leukocytes but also in the postmortem dorsolateral prefrontal cortex.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, we observed elevated blood homocysteine levels in individuals with schizophrenia and provided evidence of a causal relationship between elevated blood homo-cysteine levels and schizophrenia risk. 6,7 In addition, we showed that the methylenetetrahydrofolate reductase (MTHFR) C677T polymorphism, which causes reduced enzyme activity and elevated homocysteine levels, and common polygenic variants that are associated with plasma homo cysteine levels are risk factors for schizophrenia in the Japanese population. 6,8 Furthermore, we showed aberrant DNA methylation in patients with schizophrenia, not only in peripheral leukocytes but also in the postmortem dorsolateral prefrontal cortex.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 In addition, we showed that the methylenetetrahydrofolate reductase (MTHFR) C677T polymorphism, which causes reduced enzyme activity and elevated homocysteine levels, and common polygenic variants that are associated with plasma homo cysteine levels are risk factors for schizophrenia in the Japanese population. 6,8 Furthermore, we showed aberrant DNA methylation in patients with schizophrenia, not only in peripheral leukocytes but also in the postmortem dorsolateral prefrontal cortex. [9][10][11] Vitamin B6 is a key component in one-carbon metabolism, in which homocysteine enters the transsulfuration pathway that leads to the production of cysteine and glutathione.…”
Section: Introductionmentioning
confidence: 99%
“…Two previous meta-analyses including studies on various subgroups of patients indicated that increased Hcy level is associated with higher schizophrenia risk [12, 13]. Several mechanisms may underlie causative links between OCM disturbances and schizophrenia.…”
Section: Introductionmentioning
confidence: 99%
“…The attenuation of MTHFR as a consequence of these SNPs has been linked to elevated plasma homocysteine. Hyperhomocysteinemia has been associated with a greater risk of both SCZ and cardiovascular disease [103,104,105]. Taken together, there is a rationale establishing MTHFR as a potential candidate influencing AAEs.…”
Section: Resultsmentioning
confidence: 99%